Deskripsi Hasil Belajar Siswa Melalui Penerapan Pendekatan Self Directed Learning Pada Materi Statistika Kelas XI IPA SMA Negeri 2 Masohi - Haris Kolengsusu (Peneliti.net, 2022)
This research was conducted to determine student learning outcomes through the application of the Self Directed Learning approach. The formulation of the problem in this study is how the results of student learning on statistics material for class IX IPA 2 SMA Negeri 2 Masohi through the application of the Self Directed Learning approach. The type of research used is a quantitative descriptive research type, namely to see student learning outcomes through the application of the Self Directed Learning approach. The subjects in this study were students of class IX IPA 2 SMA Negeri 2 Masohi with a total of 26 students. Data collected through tests and observation sheets. This research was conducted from September 26 2022 to October 3 2022. By using descriptive analysis and based on the results of the research it can be concluded that applying the Self Directed Learning approach can improve student learning outcomes. This can be seen from the results of the final test of students who experienced an increase in the qualifications of 26 students, namely: 4 students (15.38%) who had very good qualifications, 5 students (19.23%) had good qualifications, 8 students (30.77%) ) sufficient qualifications and 9 students with less qualifications (34.6%), so the percentage is 34.62%. From the results obtained, it improves the learning outcomes of statistics material in class XI IPA Negeri 2 Masohi students.